Acute lower extremity paralysis after lower extremity endovascular intervention - Semi Öztürk; Muhsin Kalyoncuoğlu; Gündüz Durmuş; Adem Topçu; Mehmet Can (KARE Publishing, 2017)
A 61-year-old man underwent successful percutaneous revascularization of both lower limbs with multiple stent implantations. Paralysis of right lower limb was noticed after completion of procedure when transferring the patient from angiography table. Since hematoma compressing lumbosacral neural plexus could be a fatal complication, computed tomography (CT) image was taken. CT showed bulge of distended bladder compressing stent struts. Following placement of Foley catheter, condition improved and he was subsequently discharged uneventfully.